2020
DOI: 10.31822/jomat.768792
|View full text |Cite
|
Sign up to set email alerts
|

Environmental responsibility actions and technologies in hotels management at Fortaleza: The Case of Fortaleza-Ceará-Brazil

Abstract: This study aims to investigate the environmental responsibility actions and technologies adopted by managers at medium and large-sized hotels, of Beira Mar Avenue, in Fortaleza city. Our methodology is descriptive, using an inductive method with a qualitative approach. We applied questionnaires (structured interview) to thirteen managers of different hotels, having more than 50 housing units, classified as medium and large size, together with a systemic and non-participatory observation. Our results reveal tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…When the average value of the expression is examined, it is observed that the number of those who think that the state will contribute and those who do not are close to each other. Perinotto and Sousa (2020), in their work on environmental responsibility steps and technologies to be implemented in hotels, mention that reducing water and energy use, minimizing food waste, and making the environment greener can only be possible with the joint work of the government, hotels and non-governmental organizations.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…When the average value of the expression is examined, it is observed that the number of those who think that the state will contribute and those who do not are close to each other. Perinotto and Sousa (2020), in their work on environmental responsibility steps and technologies to be implemented in hotels, mention that reducing water and energy use, minimizing food waste, and making the environment greener can only be possible with the joint work of the government, hotels and non-governmental organizations.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…In addition to these measures, the government campaigns have been organized to create consumer awareness. Environmentalist actions have been taken to help tourists recultivate environmental behavior in destinations visited (Sabır, 2019;Olcar, 2020;Perinotto & Sousa, 2020).…”
Section: Introductionmentioning
confidence: 99%